The implementation of Free Educational Program (FEP) at MTs Syamsul Arifin Curahkalong Bangsalsari Jember. (March 2019) - Hasanah, A; Kantun, S; Soepeno, B
Abstract: The aim of this research was to analyze the implementation of FEP at MTs Syamsul Arifin Bangsalsari Jember. Education is an absolute necessity to be met throughout the lifetime in order to thrive. In Indonesia, however, not all societies were able to access education. Whereas, it was the obligation of the country to provide cheap, even free education in accordance with the mandate of the Constitution 1945 article 31. Various efforts were carried out by the Government such as scholarship, BOS, and more. However, it could not support the needs of students in education, this matter made the Regency of Jember issuing FEP Program. This research was a qualitative research by using descriptive method. Data collection method were observation, documents and interviews. The results showed that the existence of the free education program at MTs Syamsul Arifin could met the most partly of school needs. It could be seen from the increase of teacher salary than before and the capability to buy learning facilities in the form of LCD and projector.